THE PRODUCTION AND BODY COMPOSITION OF KACANG GOAT FED DIFFERENT QUALITY OF DIETS - Restitrisnani, V.; Purnomoadi, A.; Rianto, E. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
An experimental study was carried out to assess the effect of diet quality on productivity and bodycomposition of Kacang goat. Fifteen male Kacang goats weighing 14.28 ± 3.36 kg (CV = 23.55%) weredivided into 5 groups based on body weight. The experimental design used in this study wasRandomized Block Design (RBD) with 3 treatments of dietary protein and total digestible (TDN)contents (T1= diet with 9.20% protein and 54.67% TDN; T2= diet with 11.6% protein and 58.61%TDN; T3= diet with 18.33% protein and 65.23% TDN). Parameters observed were feed intake, drymatter intake, crude protein intake, TDN intake, live weight gain (LWG) and body composition ofKacang goat. The results showed that feed quality did not significantly affect (P>0.05) dry matter intakeand body composition, but significantly affect (P<0.05) protein intake, TDN intake and LWG. It can beconcluded that the higher quality diet resulted in higher productivity, but the higher quality diet was notaffect body composition of Kacang goat, except body fat gain (%).